Daun Binahong Untuk Mengurangi Jerawat Dan Kelenjar Minyak Pada Wajah - Mila Diana; Nurulisma Saputri (Garina, 2020)
Cosmetics and treatments are inseparable from the lives of women, taking care of the face part of the skin can look smooth and bright using natural ingredients. One way to take care of the face is by doing facial mask treatments made from natural, natural ingredients that can be used as masks, one of which is binahong leaves and honey. The purpose of researchers to create new innovations in the form of how to make pasta masks binahong leaves and honey. The research method is experimental method to test to several subjects according to facial skin problems, interview method conducted with respondents, observation method with respondents that include facial analysis, documentation method documenting each trialThis research experiment used binahong leaves and honey as ingredients for making face masks. Research with experimental methods and produce 3 products with different sizes, because the results of the first and second experiments researchers felt less then the researchers conducted a third product experiment that tested both models that have oily and acne face, whose use is routine once every 2 days and the results of acne and oil are reduced. The third product with a measure of 1 tablespoon of mucus binahong leaves and 1 teaspoon of honey. The benefits of binahong leaves that in addition to being used as medicines can also be used for beauty in the form of face masks binahong leaves and honey.